GREEN LEARNING BASED ON SCL IN ANALYSING FOREST BIODIVERSITY TO INCREASE THE SKILL OF STUDENTS’ SCIENCE PROCESS OF FKIP UISU MEDAN - Nurhasnah Manurung (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2020)
Before using SCL-based green learning the average level of science process skills of students or Pre Test = 23.19, after using Post Test = 65.33. Data analysis t count = 25.50> t table = 1.72 showed there was a significant increase in students' science process skills after using SCL-based green learning. For the lowest science process skills that is "applying the concept" the value of gain = 0.25 and based on the observation sheet that students are easier to classify if there are LKM guidelines and guidance as well as students do not easily believe if the observational data has not been proven. The gain value of "hypothesized" = 0.40 and based on the observation sheet hypothesized = 65% is categorized as almost sufficient. Biodiversity analysis data that 2404 individuals with 155 species were collected in transect pulls. The total number of Angyosperms sub-divisions is 132 species (115 dicotyl and 17 species of monocotyl species) and the rest are Gymnosperms and Pteridophyta subdivisions. It is known for the level of plant families in the Garden of Eden 100 of the 155 most dominant species are the Fabaceae family of which 9 species, out of a total of 72 families. Keywords:  Green Learning, SCL, Biodiversity, Science Process Skill.